HISTOLOGICAL EFFECTS OF ASCORBIC AND GLYCOLIC ACID COMBINATION ABSTRACT - Rukhsana Jabeen; Nusrat Manzoor (Journal of University Medical & Dental College, 2018)
ABSTRACT:AIM: To observe the histological eﬀects of combination of ascorbic and glycolic acid on skin. DESIGN: Experimental randomized control trial study METHODS: We selected ninety six female albino mice and randomly divided them into diﬀerent experimental and control groups. The control group A received the application of aqua base cream and the control group B received nothing while the experimental group received the combination of ascorbic and glycolic acid. All agents were applied for six weeks duration after which no treatment was given for next six weeks to see whether the eﬀects were temporary or permanent. RESULTS: The microscopic changes were like increased number of layers in epidermis and increased thickness of dermis. We used paired t-test for the calculation of p-value. CONCLUSION: The eﬀects produced were temporary and reversed after stopping the treatment. The combination of ascorbic and glycolic acid is better choice for rejuvenation.